A Survival Analysis of the Gulf Stream Warm Core Rings. Issue 10 (15th October 2020) - Silva, E. Nishchitha S.; Gangopadhyay, Avijit; Fay, Gavin; Welandawe, Manushi K. V.; Gawarkiewicz, Glen; Silver, Adrienne M.; Monim, Mahmud; Clark, Jenifer
Abstract: Survival of Gulf Stream (GS) warm core rings (WCRs) was investigated using a census consisting of a total of 961 rings formed during the period 1980–2017. Kaplan‐Meier survival probability and Cox hazard proportional models were used for the analysis. The survival analysis was performed for rings formed in four 5° zones between 75° W and 55° W. The radius, latitude, and distance from the shelf‐break of a WCR at formation all had a significant effect on the survival of WCRs. A pattern of higher survival was observed in WCRs formed in Zone 2 (70°–65° W) or Zone 3 (65°–60° W) and then demised in Zone 1 (75°–70° W). Survival probability of the WCRs increased to more than 70 % for those formed within a latitude band from 39.5° to 41.5° N. Survival probability is reduced when the WCRs are formed near the New England Seamounts. Plain Language Summary: The Gulf Stream produces warm core rings in the Western Atlantic Ocean due to its meandering nature. These warm core rings have physical, chemical, and biological impacts on shelf and slope sea regions of the Western North Atlantic. This region is one of the most highly productive fishing areas in the world, and there is a need to understand the Warm Core Ring influence on different food web systems. We use data from a 38‐yearlong (1980–2017) warm core ring census to investigate the survival probability of these warm core rings. After using multiple survival analysis techniques (a popular analysis technique in the medical and health sciences), we observed a high survival probability in WCRs formed within the 7°–65° W longitudinal band. Also, the warm core rings which demised within the 75°–70° W longitudinal band exhibited higher survival. The effect of the New England Seamount Chain (NESC) on WCR survival probabilities was revealed through a Cox proportional hazard model which showed that the further east a ring was formed from the NESC, the higher the survival probability. These findings are very important as precursors to understand the effect of WCRs on shelf‐slope processes in the Western North Atlantic. Key Points: Survival of Gulf Stream warm core rings was analyzed using Kaplan‐Meier and Cox Hazard proportional models Ring survival depends on the zone, season, latitude, and proximity to New England Seamount at formation A pattern of higher survival was observed for rings formed within 70°–65° W and then demised within 75°–70° W